2003
DOI: 10.1044/1092-4388(2003/075)
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Syntactic Processing in Individuals Who Stutter

Abstract: Syntactic processing was explored in individuals who stutter (IWS). Grammaticality judgments and event-related brain potentials (ERPs) were obtained while participants read sentences, half containing verb-agreement violations. Grammaticality judgments for an offline verb-agreement task did not differ between IWS and normal speakers (NS). However, judgment accuracy of IWS for the online task was lower than that of NS, particularly for verb-agreement violations that occurred in longer and more syntactically comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This finding was unexpected given Weber-Fox et al’s [ 18 ] observation that preschool-age CWS exhibited a P600 reduced over the left hemisphere and increased over the right hemisphere relative to fluent peers. A reduced and narrowly distributed P600 was also reported in AWS compared to fluent controls [ 51 ]. Although the language skills of the AWS group were within normal limits, this group performed worse than controls on linguistic assessments.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding was unexpected given Weber-Fox et al’s [ 18 ] observation that preschool-age CWS exhibited a P600 reduced over the left hemisphere and increased over the right hemisphere relative to fluent peers. A reduced and narrowly distributed P600 was also reported in AWS compared to fluent controls [ 51 ]. Although the language skills of the AWS group were within normal limits, this group performed worse than controls on linguistic assessments.…”
Section: Discussionmentioning
confidence: 98%
“…ERP studies of adults who stutter (AWS) revealed atypical neural activity during semantic and syntactic processing relative to adults who do not stutter (AWNS), despite their having normal linguistic abilities [ 51 53 ]. In a natural speech processing paradigm, Weber-Fox and Hampton [ 53 ] observed semantic (verb expectation) and syntactic (verb agreement) violations in simple sentences respectively elicit typical N400 and P600 effects in AWNS.…”
Section: Introductionmentioning
confidence: 99%
“…The former findings were taken to indicate that neural functions related to lexical retrieval may be altered in AWS, while the latter findings were taken to indicate that adulthood stuttering may not stem from phonological processing deficits. This line of work has also been extended to investigate syntactic processing in AWS (e.g., Cuadrado and Weber-Fox, 2003; Weber-Fox and Hampton, 2008). As discussed in Maxfield et al (2012), it remains an open question whether differences observed between AWS and TFA in receptive language processing generalize to language production (although see Pickering and Garrod, 2007, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Weber-Fox and colleagues have reported that AWS exhibit atypical ERP activity during sentence processing (Cuadrado and Weber-Fox, 2003), including atypical N400 activations (Weber-Fox, 2001; Weber-Fox and Hampton, 2008). It is important to acknowledge that activation spreading mechanisms driving N400 priming effects in the picture-word tasks we have adopted may be different from mechanisms that drive N400 effects elicited during sentence processing.…”
Section: Discussionmentioning
confidence: 99%